Northward propagation of Andean genesis: Insights from Early Cretaceous synorogenic deposits in the Aysén-Río Mayo basin - Gianni, Guido Martin (2020)
Decoding the earliest orogenic stages in the Andes, the largest subduction orogen on Earth is fundamental to understanding changes in climate, drainage organization, and biodiversity in South America. Furthermore, it is crucial to unraveling the driving mechanism behind the initiation of orogeny. To track the earliest stages of Andean growth, we studied the Aysén/Río Mayo basin (ARB) in the North Patagonian Andes. The small degree of Cenozoic tectonic overprinting in this part of the Andes has allowed outstanding preservation of the deformational and sedimentary record of the earliest Andean deformation. In this study, we employ a multidisciplinary approach involving structural geology, sedimentology, geochronology, and provenance studies from the Early Cretaceous Apeleg Formation (~130?122 Ma) in the ARB and geochemical analysis of intrusive Cretaceous igneous rocks. Particularly, the recognition of syncontractional growth strata at several localities indicate a syntectonic origin for this unit and provide additional structural evidence of Early Cretaceous contraction in the North Patagonian Andes. Thus, the Apeleg Formation is interpreted as deposited during a contractional basin stage. Geochemical data from Aptian-Albian intrusive igneous rocks indicate that initial contraction emplaced over thinned crust likely inherited from the Jurassic extension in the ARB. This stage is then compared with a new synthesis of the earliest Cretaceous contraction along the Andes. This analysis reveals that the ARB likely holds the oldest post-Gondwanic synorogenic unit along the orogen and more significantly, that Andean birth was a diachronous process which propagated northward since the late Early Cretaceous. The latter findings have major implications for the evolution of the Andes and shed light into the driving mechanism behind initial orogeny.